A Study on Financial Literacy and Its Determinants among Gen Y Employees in Coimbatore City - MSekar,; Gowri , M (Gyan Management Journal, 2014)
Financial literacy is the mix of one's knowledge, skill and attitude towards financial matters. It helps to ---.:ike informed decisions and well being of an individual. Research has been conducted globally for ---.easuring the level of financial literacy. And also financial literacy survey has been conducted at :::,untry level by the governments. Most of the surveys have thrown light on their poor level of financial ::eracy. This study focuses on financial literacy among Generation Y employees and to examine how ,.-ell-equipped they are to make financial decisions. An attempt has been made through this study to "'leasure the level of financial literacy of Gen Y employees. Findings of the study depict that gender,
Keywords: Financial Literacy; Financial decisions; Gen Y.